Alat Komunikasi Darurat dengan ESP8266 dan LoRa untuk Pendaki Gunung - Fauzan, Mochamad Farras; Siskandar, Ridwan; Falah, Naufal Alif; Maulana, Muhammad Shubhi; Balle, Joddy Lintar; Febriyanti, Tria; Suhada, Vandame Ronald; Wirastuti, Merry Ardelia; Fakhiratunisa, Nabila; Al-ars, Kaisar Renaisance; Kusumah, Billi Rifa (Jurnal Sains Indonesia, 2021)
Public interest in climbing activities is increasing over time. This activity is a dangerous activity if it is not equipped with good climbing knowledge. There are many cases of climbers who are dissapear or lost on the mountain, one reason is the lack of information about the path and terrain of the climb that will be traversed. This can be avoided if the climbers have good communication and coordination. So that climbers who have lost their way can get back on the right track thanks to good communication and coordination. This research proposes to build a communication tool that uses radio signals to communicate and has a GPS (Global Positioning System). Later climbers can communicate and see other climbers who have this tool through a browser that is owned by their smartphone.